Modeling and control of engines and drivelines - Eriksson, Lars; Nielsen, Lars (Automotive series, 2014)
Control systems have come to play an important role in the performance of modern vehicles with regards to meeting goals on low emissions and low fuel consumption. To achieve these goals, modeling, simulation, and analysis have become standard tools for the development of control systems in the automotive industry.